Hey there, I am currently doing a coursework on finding roots using the 3 methods - Change in Sign method, Newton Raphson, and finally rearranging the equation f(x)=0 into the form x=g(x).
I've finished the first two parts of the coursework, but I am stuck on this last bit. I must rearrange 0 = -5.1x^3 + 9.06x^2 + x + 1.3 into the aforementioned form, but I don't exactly understand how. I have rearranged it into x ( 5.1x^2 - 9.06x ) - 1.3 = x, but I honestly don't understand if this is correct.
Please help, thanks.